PARTICLES, DNA AND RNA - CLUBY, JOHN (2023)
The present invention provides competitive particles (e.g., virus-like particles, RNA, and DNA) for treating or preventing viral infections and methods of using such particles to treat or prevent or reduce the risk of viral infections (or symptoms thereof) in a subject (e.g., a human or animal subject). For example, the method herein is a method of reducing or reducing the establishment of a human-livestock diseased population of viruses in an animal, such as a livestock or wild animal (e.g., bat, camelidae, or squama (e.g., pangolin). 本发明提供了用于治疗或预防病毒感染的竞争性颗粒(如病毒样颗粒、RNA和DNA)以及使用此类颗粒治疗或预防受试者(如人或动物受试者)的病毒感染(或其症状)或降低其风险的方法。例如，本文的方法是一种减少动物，如家畜或野生动物(例如蝙蝠、骆驼科动物或鳞甲目(例如穿山甲))中病毒的人畜共患病群体或减少所述群体的建立的方法。